Risk factors of immune checkpoint inhibitor-associated acute kidney injury: evidence from clinical studies and FDA pharmacovigilance database - Chen, Pengwei; Zhu, Jianhong; Xu, Yanchun; Huang, Qiuyan; Su, Jianan; Gao, Ziqing; Feng, Min (BMC nephrology, 2023)
Background Several risk factors of immune checkpoint inhibitors (ICIs)-associated acute kidney injury (AKI) have been reported sporadically. To identify the risk factors of ICIs-associated AKI in a large-scale population, therefore we conducted a systematic review and a real-world retrospective study. Methods We search literature concerning risk factors of ICIs-associated AKI in ClinicalTrials.gov and electronic databases (PubMed, Cochrane Library, Embase) up to January 2022. Meta-analysis was performed by using odds ratios (ORs) with 95%CIs. In a separate retrospective pharmacovigilance study by extracting data from US FDA Adverse Event Reporting System (FAERS) database, disproportionality was analyzed using the reporting odds ratio (ROR). Results A total of 9 studies (5927 patients) were included in the meta-analysis. The following factors were associated with increased risk of ICIs-associated AKI, including proton pump inhibitors(PPIs) (OR = 2.07, 95%CI 1.78–2.42), angiotensin-converting enzyme inhibitors (ACEIs)/ angiotensin receptor blockers (ARBs) (OR = 1.56, 95%CI 1.24–1.95), nonsteroidal anti-inflammatory drugs (NSAIDs) (OR = 1.29, 95%CI 1.01–1.65), diuretics (OR = 2.00, 95%CI 1.38–2.89), diabetes mellitus (OR = 1.28, 95%CI 1.04–1.57), genitourinary cancer (OR = 1.46, 95%CI 1.15–1.85), combination therapy of ICIs (OR = 1.93, 95%CI 1.25–2.97) and extrarenal immune-related adverse events(irAEs) (OR = 2.51, 95%CI 1.96–3.20). Furthermore, analysis from FAERS database verified that concurrent exposures of PPIs (ROR = 2.10, 95%CI 1.91–2.31), ACEIs/ARBs (ROR = 3.25, 95%CI 2.95–3.57), NSAIDs (ROR = 3.06, 95%CI 2.81–3.32) or diuretics (ROR = 2.82, 95%CI 2.50–3.19) were observed significant signals associated with AKI in ICIs-treated patients. Conclusions Concurrent exposures of PPIs, ACEIs/ARBs, NSAIDs or diuretics, diabetes mellitus, genitourinary cancer, combination therapy, and extrarenal irAEs seem to increase the risk of AKI in ICIs-treated patients.